Review: analysis of optimal conditions of bovine serum albumin (BSA) protein denaturation inhibition method in anti-inflammatory activity testing of various plant leaf extracts - Nirmala, Annisa Rizka; Permatasari, Lina; Muliasari, Handa; Deccati, Rizqa Fersiyana (Journal of Agritechnology and Food Processing, 2023)
Inflammation is a manifestation of the immune response to eliminate antigens and a process to respond to tissue damage. There are various drugs to control and suppress inflammation, referred to as anti-inflammatory agents. One method to test anti-inflammatory activity is the inhibition of Bovine Serum Albumin (BSA) protein denaturation. This review article will discuss the stages and optimal conditions in the inhibition of BSA protein denaturation method using various leaf extract samples. Literature was gathered from several journal database websites such as PubMed, ScienceDirect, and Google Scholar with keywords "anti-inflammatory," "inhibition of BSA protein denaturation," and "leaf extract," spanning publication years from 2002 to 2023. The results of anti-inflammatory activity tests can be expressed as either percentage inhibition or IC50 values. Optimal conditions were obtained by preparing a 0.2% BSA solution with Tris Buffer Saline (TBS), maintaining a 9:1 composition ratio between the BSA solution and the sample, and heating at an optimal denaturation temperature of 70 °C. Before conducting tests using this method, it is crucial to ensure that the suspected active compounds with anti-inflammatory activity are not degraded at this heating temperature.